Flouting of Conversational Maxims In “Avengers: Endgame” Movie - Dewa Ayu Indra Widiani; Komang Dian Puspita Candra,; Ni Wayan Suastini (IJELAL (International Journal of English Learning and Applied Linguistics), 2021)
To achieve the goals of communication, it is important for the participants in every conversation to obey the cooperative principle in order to avoid misunderstanding of interpretation between them. This research deals with the study of flouting maxim in a superhero movie entitled Avengers: Endgame movie. This research focuses on analysing the types of flouting maxim in Avengers: Endgame movie flouted the maxims. The researcher used the theory of cooperative principle proposed by Grice (1975) to analyse the types of flouting maxim. The researcher used descriptive qualitative method to describe the data to answer the problems of the study. The result of the study shows that there are 20 data of flouting maxim in Avengers: Endgame movie. The highest occurrence of flouting maxim in this movie is flouting maxim of quantity and quality with 7 data (35%). Then followed by flouting maxim of relevance with 4 data (20%). Flouting maxim of manner is the lowest occurrence of flouting maxim with 2 data (10%).